2012
DOI: 10.4236/ajps.2012.33039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gamma Irradiation on Morpho-Agronomic Characteristics of Soybeans (<i>Glycine max</i> L.)

Abstract: Mutation breeding in crop plants is an effective approach in improvement of crop having narrow genetic base such as soybean. The main objective of the present study is to determine the effect of different doses of gamma irradiation on different morpho-agronomic characteristics. Agronomic traits that were analyzed included; grain yield, number of pods/plant, number of seeds/plant and weight of 100 seeds and numbers of days to 50% flowering. Morphometric characterization of the descriptive data included plant he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
44
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 16 publications
11
44
0
10
Order By: Relevance
“…This is in accordance with report [25][26][27] in soybean, observed that the exposure of gamma irradiation influence the plant height moderately. However in M2 generation it was observed that the plant height was significantly altered.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is in accordance with report [25][26][27] in soybean, observed that the exposure of gamma irradiation influence the plant height moderately. However in M2 generation it was observed that the plant height was significantly altered.…”
Section: Discussionsupporting
confidence: 82%
“…High yielding and early maturing barley plants were developed by mutation breeding methods [35]. Highest grain yield increase in soybean irradiated with 20KR of gamma rays was reported [27]. The increase in the grain yield can also be correlated with the increase in the average leaf area per plant by 20KRC and 40KRC treatments, which potentially increased the growth rate and hence stimulating the average grain yield of Amaranthus caudatus.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the average values of seed per plant presented a negative trend by increasing the radiation dosage. Such decreasing trends were also reported by Mudibu et al, (2012) and Fe et al, (2000). The quadratic model was the one with a greater adjust to the observed data since it displayed an adjusted coefficient of determination of 81.57%, and a Mallow's Cp lower value (2.4319) ( Table 4 and Figure 1D).…”
Section: Number Of Seeds Per Plantsupporting
confidence: 70%
“…Mutasi dengan sinar gamma juga meningkatkan kandungan beberapa asam amino esensial biji kedelai (Soedarti et al 2011). Mudibu et al (2012) melaporkan generasi M2 menghasilkan berat biji dan ukuran biji kedelai meningkat. Sing et al (2015) mengumpulkan laporan beberapa peneliti dan menyimpulkan tanaman kedelai yang mengalami mutasi buatan dapat menyebabkan perubahan sifat-sifat morfologis dan fisiologis, yaitu tinggi tanaman menjadi lebih tinggi dan lebih pendek, perubahan tipe pertumbuhan determinate menjadi indeterminate, batang lebih tebal, ruas lebih pendek, biji bisa lebih cepat masak, jumlah polong lebih banyak, dan produksi biji lebih tinggi.…”
Section: Pendahuluanunclassified
“…Hasil penelitian Mudibu et al (2012) pada tanaman kedelai yang diradiasi sinar gamma dosis 200400 Gy juga menunjukkan penurunan dihampir semua sifat agronomi dan morfologi termasuk tinggi tanaman dan diameter batang. Sementara peneliti lain juga melaporkan penurunan sifat akibat peningkatan dosis sinar gamma seperti pada pertumbuhan tanaman kacang merah (Nouri & Tavassoli 2012) bibit kacang gude (Cajanus cajan) (Desai & Rao 2014), bibit bawang merah (Kebeish et al 2015), dan bibit jarak pagar (Songsri et al 2011).…”
Section: Pengaruh Radiasi Sinar Gamma Cobalt 60 Dan Varietas Jagung Punclassified